Natural products: potential therapeutic agents for atherosclerosis - CHENG, Xiaobei; ZHAO, Caili; JIN, Zhiwei; HU, Jianping; ZHANG, Zhenzhen; ZHANG, Chao (Chinese journal of natural medicines, 2022)
Atherosclerosis (AS) is an invisible killer among cardiovascular diseases (CVD), which has seriously threatened the life of quality. The complex pathogenesis of AS involves multiple interrelated events and cell types, such as macrophages, endothelial cells, vascular smooth muscle cells and immune cells. Currently, the efficacy of recommended statin treatment is not satisfactory. Natural products (NPs) have attracted increasing attention with regard to their broad structural diversity and biodiversity, which makes them a promising library in the demand for lead compounds with cardiovascular protective bio-activity. NPs can preclude the development of AS by regulating lipid metabolism, ameliorating inflammation, stabilizing plaques, and remodeling the gut microbiota, which lays a foundation for the application of NPs in clinical therapeutics.